Patterns of cervical node positivity, regional failure rates, and fistula rates for HPV+ oropharyngeal squamous cell carcinoma treated with transoral robotic surgery (TORS). (November 2018) - Cannon, Richard B.; Houlton, Jeffrey J.; Patel, Sapna; Raju, Sharat; Noble, Anisha; Futran, Neal D.; Parvathaneni, Upendra; Méndez, Eduardo
Highlights: Survival and recurrence outcomes are excellent after transoral robotic surgery. Cervical node positivity was 93%, 84% in level IIa. Neck dissection of levels II–IV is sufficient to accurately stage the neck and prevent regional recurrences. Single-staged operations did not result in any postoperative pharyngocutaneous fistula. Abstract: Objectives: (1) Report the patterns of cervical node positivity for HPV + oropharyngeal squamous cell carcinoma (OPSCC) treated with transoral robotic surgery (TORS) and a unilateral level II–IV node dissection. (2) Investigate the regional failure rate following this operation. (3) Report the rate of pharyngocutaneous fistula (PCF) formation intraoperatively and postoperatively following TORS/neck dissection. Methods: Retrospective case series of 88 patients with HPV+ OPSCC treated with TORS and simultaneous neck dissection levels II–IV at the University of Washington from 2010 to 2016. Primary endpoints were PCF, regional recurrence, disease-free survival (DFS), and overall survival (OS). Results: The overall frequency of cervical node positivity was 93%, with 84% in level IIa, 7% in IIb, 23% in III, and 13% in IV. Two patients developed PCF intraoperatively, repaired with a local digastric flap, and no postoperative PCF occurred. Sixteen patients (18%) received surgery alone, 49 patients (56%) received adjuvant radiation, and 23 patients (26%) underwent adjuvant chemoradiation. DFS at 2 years was 95% and OS at 2 years was 100%. No concerning level Ib nodes were identified preoperatively or during surgery, and no regional failures occurred in this location. Conclusion: Our data suggests, in TORS for HPV+ OPSCC, neck dissection of levels II–IV accurately stages the neck pathologically and prevents regional recurrences, with adjuvant therapy when indicated, and survival outcomes are excellent. Single-staged operations did not result in any postoperative PCF. Avoiding dissection of level Ib with TORS oropharyngectomy limits morbidity to the marginal mandibular nerve and salivary function, and resulted in no postoperative fistulas with minimal reconstruction interventions.